Prospects of Coupled Organic–Inorganic Nanostructures for Charge and Energy Transfer Applications. Issue 3 (17th September 2020) - Steiner, Anja Maria; Lissel, Franziska; Fery, Andreas; Lauth, Jannika; Scheele, Marcus
Abstract: We review the field of organic–inorganic nanocomposites with a focus on materials that exhibit a significant degree of electronic coupling across the hybrid interface. These nanocomposites undergo a variety of charge and energy transfer processes, enabling optoelectronic applications in devices which exploit singlet fission, triplet energy harvesting, photon upconversion or hot charge carrier transfer. We discuss the physical chemistry of the most common organic and inorganic components. Based on those we derive synthesis and assembly strategies and design criteria on material and device level with a focus on photovoltaics, spin memories or optical upconverters. We conclude that future research in the field should be directed towards an improved understanding of the binding motif and molecular orientation at the hybrid interface. Abstract : This Review provides an overview of the field of organic–inorganic nanocomposites with a focus on materials that exhibit a significant degree of electronic coupling across the hybrid interface. The characteristic properties of these nanocomposites pave the way to potential optoelectronic applications in devices which exploit singlet fission, triplet energy harvesting, photon upconversion or hot charge carrier transfer.